2013
DOI: 10.5380/ce.v18i2.32590
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação De Protocolo De Prevenção De Úlcera Por Pressão No Contexto Domiciliar: Uma Trajetória Percorrida

Abstract: RESUMO:A prevenção de úlceras por pressão é mais eficaz e economicamente viável que seu tratamento, para tal há protocolos padronizados e normativos. O objetivo deste estudo foi verificar a influência da aplicação de um protocolo de enfermagem para a prevenção de úlceras por pressão em idoso acamado no domicílio. Esta pesquisa dividiu-se em duas etapas: a validação de conteúdo por enfermeiras especialistas em estomaterapia e a validação clínica com pacientes idosos com risco de desenvolver esses agravos. Foi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…The methodological delineations described in the research differ, but we identified a predominance of quasi-experimental (20)(21)(22) Chart 2 -Characterization of the nine quantitative articles analyzed, 2018 Park, Kim (22) , 2015 and transversal studies (23)(24)(25) , as well as experimental (26)(27) and longitudinal studies (28) . With regards to the results, the authors stated that educational interventions could be considered a good practice to be promoted by nurses, who provide care for elders in home care, as well as an instrument that favors the adoption of other good care practices for their daily lives.…”
Section: Synthesis Of Results Of Quantitative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodological delineations described in the research differ, but we identified a predominance of quasi-experimental (20)(21)(22) Chart 2 -Characterization of the nine quantitative articles analyzed, 2018 Park, Kim (22) , 2015 and transversal studies (23)(24)(25) , as well as experimental (26)(27) and longitudinal studies (28) . With regards to the results, the authors stated that educational interventions could be considered a good practice to be promoted by nurses, who provide care for elders in home care, as well as an instrument that favors the adoption of other good care practices for their daily lives.…”
Section: Synthesis Of Results Of Quantitative Studiesmentioning
confidence: 99%
“…The important role of nursing in health promotion and active aging was evidenced in the authors' conclusions, which described satisfactory and positive outcomes. The described actions were performed in several environments, ranging from homes to hospitals (27) .…”
Section: Data Collection Data Analysis Categories Identifiedmentioning
confidence: 99%
“…Nesse contexto, pôde-se observar no caso relatado a garantia da integralidade do cuidado à paciente, ao ser referenciada da APS à atenção especializada para desbridamento da ferida infectada, e, após o procedimento, retornar para continuidade dos cuidados na APS. Assim, cabe destacar que para prestar assistência integral e com qualidade, devem ser consideradas as dificuldades relacionadas aos idosos, à própria condição social e o vínculo do idoso com sua família como provedora de condições para a prestação de cuidados 10 .…”
Section: Discussionunclassified
“…inconsciência; imobilização; insuficiência sensorial; perda de função motora; incontinência urinária e/ ou fecal; deficiências nutricionais; índice de massa corporal alterados; doenças circulatórias; imunodeficiência; uso de corticoides por tempo prolongado; tabagismo; e alterações do nível de consciência (5) .…”
Section: Metodologiaunclassified